2021
DOI: 10.1111/jgh.15633
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, sepsis, and organ failure in hospitalized patients with cirrhosis vary by type of infection

Abstract: Background and Aim: Infection is associated with substantial morbidity and mortality in cirrhosis, but presumably, not all infections carry the same risk of mortality. We compared outcomes of different sites of infection in a nationally representative sample of inpatients with cirrhosis. Methods: We queried the Nationwide Readmissions Database for patients with cirrhosis from 2011 to 2014. Cirrhosis and infection diagnoses were identified by previously used algorithms of ICD-9 codes. The following infections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Pneumonia, SBP, and CDI had notably higher mortality than cellulitis and UTI, and sepsis and organ failure were also more common. Pneumonia had the highest mortality in the multivariate regression analysis (OR 2.73, 95%CI 2.68-2.80) and caused multiple organ failure (OR 3.59, 95%CI 3.50-3.68)[ 108 ]. The prevalence of CDI in cirrhosis has shown an increasing trend at approximately 2.7% in 2014, while the mortality of CDI is on the decline, and in local hospitals, the incidence of CDI ranges from 4.9% to 18.8%[ 109 ].…”
Section: Epidemiology Of Major Complicationsmentioning
confidence: 99%
“…Pneumonia, SBP, and CDI had notably higher mortality than cellulitis and UTI, and sepsis and organ failure were also more common. Pneumonia had the highest mortality in the multivariate regression analysis (OR 2.73, 95%CI 2.68-2.80) and caused multiple organ failure (OR 3.59, 95%CI 3.50-3.68)[ 108 ]. The prevalence of CDI in cirrhosis has shown an increasing trend at approximately 2.7% in 2014, while the mortality of CDI is on the decline, and in local hospitals, the incidence of CDI ranges from 4.9% to 18.8%[ 109 ].…”
Section: Epidemiology Of Major Complicationsmentioning
confidence: 99%
“…In a study conducted in an extensive commercial database in the US, the prevalence of CDI in cirrhosis was 134.93 per 100,000 of 133,400 patients diagnosed with cirrhosis between 2018–2021 [ 30 ]. Nationwide Readmissions Database (NRD) in the US revealed that the prevalence of CDI in patients with cirrhosis was 2.8% from 2011 to 2014, with higher inpatient mortality compared with cellulitis and urinary tract infections (UTI) (17.6% vs. 7.6%, 11.8%), respectively, and the presence of sepsis and organ failure was also most common in CDI [ 31 ]. Another study using the National Inpatient Sample (NIS) [ 32 ], which investigated trends in CDI hospitalizations for end-stage liver disease (ESLD) from 2005 to 2014, found that the prevalence of CDI among inpatients with decompensated cirrhosis increased approximately twofold from 1.3% in 2005 to 2.7% in 2014, with an annual rate of increase of 7.8%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Therefore, understanding and predicting the prognosis of this population is essential to mitigate the risk of undesirable outcomes. Extensive publications have reported increased mortality of CDI in patients with cirrhosis [ 22 , 23 , 31 , 33 , 34 , 36 , 39 , 44 , 47 , 48 , 59 ]. However, one study has not established the impact of CDI development on mortality in patients with cirrhosis and SBP receiving norfloxacin as secondary prophylaxis [ 37 ].…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Цирроз печени (ЦП) является одной из острых проблем здравоохранения в связи с большой распространенностью во всем мире, развитием различных осложнений и значительным снижением качества жизни больных [1]. К числу наиболее часто встречающихся осложнений при ЦП относятся инфекции (пневмония, инфекции мочевыводящих путей, инфицированный асцит, спонтанный бактериальный перитонит) [2], наблюдающиеся у 47% госпитализированных пациентов [3] и являющиеся триггером декомпенсации ЦП [4]. Анализ литературных источников свидетельствует о том, что в настоящее время много внимания уделяется изучению при ЦП факторов риска, патогенетических механизмов инфекционных осложнений, в том числе роли иммунологических расстройств в развитии осложнений ЦП [5,6].…”
unclassified